Leishmania infection-induced multinucleated giant cell formation via upregulation of ATP6V0D2 expression - Hong, Jing; Sanjoba, Chizu; Fujii, Wataru; Yamagishi, Junya; Goto, Yasuyuki (Frontiers in Cellular and Infection Microbiology, 2022)
Leishmaniasis is caused by infection with protozoan parasites of the genus Leishmania. In both clinical and experimental visceral leishmaniasis, macrophage multinucleation is observed in parasitized tissues. However, the feature and the mechanism of macrophage multinucleation remained unclear. Here we report that infection of Leishmania donovani, a causative agent of visceral leishmaniasis, induces multinucleation of bone marrow derived macrophages (BMDMs) in vitro. When these infection-induced multinucleated macrophages were compared with cytokine-induced multinucleated giant cells, the former had higher phagocytic activity on red blood cells while no apparent changes on phagocytosis of latex beads. BMDMs infected with L. donovani had increased expression of ATP6V0D2, one of the components of V-ATPase, which was also up-regulated in the spleen of infected mice. Infection-induced ATP6V0D2 localized in a cytoplasmic compartment which did not overlap with mitochondria, endoplasmic reticulum or lysosomes. When ATP6V0D2 expression was recombinantly induced in BMDMs, formation of multinucleated macrophages was induced as seen in the infected macrophages. Taken together, L. donovani infection induces multinucleation of macrophages via ATP6V0D2 up-regulation leading to unique metamorphose of the macrophages towards hemophagocytes.